1999
DOI: 10.1128/jvi.73.11.9237-9246.1999
|View full text |Cite
|
Sign up to set email alerts
|

Sendai Virus Gene Start Signals Are Not Equivalent in Reinitiation Capacity: Moderation at the Fusion Protein Gene

Abstract: In paramyxovirus transcription, viral RNA polymerase synthesizes each monocistronic mRNA by recognizing the gene start (S) and end (E) signals flanking each gene. These signal sequences are well conserved in the virus family; nevertheless, they do exhibit some variations even within a virus species. In Sendai virus (SeV) Z strain, the E signals are identical for all six genes but there are four (N, P/M/HN, F, and L) different S signals with one or two nucleotide variations. The significance of these variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Previously, a hyperfusogenic phenotype was also observed with mutants of the F protein of parainfluenza virus 5 (previously called simian virus 5) in which the fusion peptide was modified by glycine-to-alanine substitutions, suggesting that the native glycine residues serve to reduce the efficiency of fusion (15). Wild-type Sendai virus also downregulates its fusion activity, in this case due to a difference in a transcription gene start signal that results in reduced F gene transcription and protein expression; correction of this difference results in a virus that replicates more efficiently and is more lethal (17). A number of other paramyxoviruses also downregulate F expression (5,40,42).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a hyperfusogenic phenotype was also observed with mutants of the F protein of parainfluenza virus 5 (previously called simian virus 5) in which the fusion peptide was modified by glycine-to-alanine substitutions, suggesting that the native glycine residues serve to reduce the efficiency of fusion (15). Wild-type Sendai virus also downregulates its fusion activity, in this case due to a difference in a transcription gene start signal that results in reduced F gene transcription and protein expression; correction of this difference results in a virus that replicates more efficiently and is more lethal (17). A number of other paramyxoviruses also downregulate F expression (5,40,42).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been reported that Sendai virus (SeV) and human parainfluenza virus type 1 (hPIV1) also possess strategies to inhibit production of the F protein (8,24). Kato et al showed that SeV inhibits production of the F protein and its downstream H and L proteins by having a unique GS signal at the F gene and thus reducing the reinitiation rate of transcription at the M-F gene boundary (24). The mutant SeV, in which the GS signal at the F gene was replaced by the common GS signal found at the P, M, and HN genes, replicated more efficiently and showed higher virulence in mice than the parental SeV (24).…”
Section: Discussionmentioning
confidence: 99%
“…As it has been documented in numerous studies, the GS and GE signals of the vector virus can efficiently direct the expression of an exogenous protein [60]. Although GS and GE signals are often highly conserved along the viral genome, there might be variations in their sequences and transcription efficacy [142]. Flanking the sequence of GFP inserted into the 6 th genome position of PIV5 with GS/GE specific for either 2 nd or 7 th gene junctions resulted in large differences The 5'-end of a genome contains a trailer sequence (tr) of a variable length, ranging from 50 up to 707 nucleotides [121,133].…”
Section: Principles Of Exogene Insertionsmentioning
confidence: 99%